Study guides

☆☆

Q: What is (4x plus 3 ) plus (-2x plus 8)?

Write your answer...

Submit

Related questions

2x - 5 - 4x + 8= 2x - 4x - 5 + 8= -2x + 3

Simplify 4x + 3 = 2x + 8 2x = 5 x =2½

4x + 3 = -3 + 2x + 14 2x + 3 = -3 +14 2x + 3 = 11 2x = 8 x=4

X= -8

3x-5

It is: 11-6x as a simplified expression

The derivative of 2x2 + 4x + 8 is 4x+4.

(2x - 8)(-4x + 4) = -8x2 + 40x - 32

2x + 3 + 3x = x + 11 5x + 3 = x + 11 4x + 3 = 11 4x = 8 x = (8/4) x = 2

4x - 3 = 2x + 54x - 2x = 5 + 32x = 8x = 8/2x = 4To check:4(4) - 3 = 132(4) + 5 = 13

Lets simplify the above given equation : -8 plus 6(-x - 3) plus 4x simplified as : -8-6x -18 +4x =-2x -26 . =-2(x+13).

x=5

2x/3 = 8 + 4x2x = 24 + 12x-24 = 10x-2.4 = x

2x-4=6x+8-8= -82x-12= 6x-2x= -2x-12= 4x/4=/4-3=x

that answer is 9

1)add 5 to each side ,2x+8=4x 2)subtract 2x from each side, 8=2x 3) divide each side by 2, x=4

4x + 2y = -8 → 2y = -4x - 8 → y = -2x - 4

It is 6x+1 simplified

5 - 2x = 8 x = -1 and 1/2 4x = 6 x = 6/4 or 3/2

If you mean integral[(2x^2 +4x -3)(x+2)], then multiply them out to get: Integral[2x^3+8x^2+5x-6]. This is then easy to solve and is = 2/4x^4+8/3x^3+5/2x^2-6x +c

The given expression can be simplified to: -6x-7

-4x - 8 = -2x + 12Add 4x to each side:-8 = 2x + 12Subtract 12 from each side:-20 = 2xDivide each side by 2:-10 = x

2X + 8^2 = 2X+64, for whatever value X. If the question is (2x+8)², the answer is 4x²+32x+64 The formula is (a+b)² = a² + 2ab + b². a=2x, b=8, a²=4x², b²=64

2x-8+4x=468+46=542x+4x=6x6x divided by 54 equals 9.:)Hope I Helped! :D

It is an expression that can be simplified to: 6x+1